Metode Numerik Untuk Menentukan Harga Opsi Dengan Model Volatilitas Leland - arsyad L (IAIN Palopo, 2020)
Option price under transaction cost with leland volatility model is the solution of a non linear diferential equations. To solve this equation used numerical methods based on an upwind finite difference for spatial discretization as well as the use of explicit and implicit methods for discretizing time-stepping. upwind finite difference method with explicit time-stepping scheme proved to be unstable so as not konvegen. While the use of implicit time-stepping scheme is proved monotonous, consistent and stable so that converge to the viscosity solution.